Cost-utility analysis of dynamic intraligamentary stabilization versus early reconstruction after rupture of the anterior cruciate ligament - Martin Bierbaum; Oliver Schöffski; Benedikt Schliemann; Clemens Kösters (Health Economics Review, 2017)
Objectives: The aim of this study was to evaluate the cost-effectiveness of the dynamic intraligamentary stabilization (DIS) technique in comparison with reconstructive surgery (ACLR) in the treatment of isolated anterior cruciate ligament (ACL) ruptures from the perspective of the community of insured citizens in Germany. Methods: Because of the specific decision problem at hand, namely that with DIS the procedure has to take place within 21 days after the initial trauma, a decision tree was developed. The time horizon of the model was set to 3 years. Input data was taken from official tariffs, payer data, the literature and assumptions based on expert opinion when necessary. Results: The decision tree analysis identified the DIS strategy as the superior one with 2.34 QALY versus 2.26 QALY for the ACLR branch. The higher QALY also came with higher costs of 5,398.05 exteuro for the DIS branch versus 4,632.68 exteuro for the ACLR branch respectively, leading to an ICER of 9,092.66 exteuro per QALY. Results were robust after sensitivity analysis. Uncertainty was examined via probabilistic sensitivity analysis resulting in a slightly higher ICER of 9,567.13 exteuro per QALY gained. Conclusion: The DIS technology delivers an effective treatment for the ACL rupture at a favorable incremental cost-effectiveness ratio. Electronic supplementary material: The online version of this article (doi:10.1186/s13561-017-0143-9) contains supplementary material, which is available to authorized users.
Keywords: 330